GAMBARAN KADAR ZINK (Zn) PADA IBU HAMIL TRIMESTER I, TRIMESTER II, dan TRIMESTER III DI LABORATORIUM KLINIK PRODIA KRAMAT - Desi Aryani (UNIVERSITAS SARI MUTIARA INDONESIA, 2020)
The concentration of zinc (Zn) in pregnant women is relatively decreased by 35%. Low Zn in pregnant women can reduce the transport of nutrients to the uterus and affect the provision of adequate nutrition to the baby. Zn deficiency in pregnant women can cause several complications, including low birth weight (LBW), Intrauterine Growth Restriction (IUGR), and preterm birth. Zn is important in maintaining the stability of physiological functions, the process of DNA formation in the fetus and cell hemostasis. This study used a cross-sectional approach using medical record data in the Laboratory of the Prodia Kramat Clinic in Central Jakarta in 2019 - 2020. The sample in this study was non-probability sampling with a purposive sampling approach based on limiting criteria as many as 37 pregnant women. Based on the results of the analysis, it is known that 392 (91.4%) pregnant women have not realized the importance of Zn examination, the highest reduction in Zn levels in pregnant women occurred in the second trimester as much as 86.5%, at the age level of 26-30 years. This can occur due to the lack of Zn supplementation during pregnancy and lack of awareness in monitoring the nutritional components both macronutrient and micronutrient, one of which is Zn. Keywords : Pregnant Women, Nutrition, Trimester, Zinc